Synthesis and Evaluation of Substituted Aryl Thiazoles With Antioxidant Potential as Gastro-sparing Anti-inflammatory Agents - Bansal, Akhil; Bali, Alka; Balaini, Ajitesh (Letters in Drug Design & Discovery, 2020)
Background: NSAIDs are used as first-line drugs for the treatment of various inflammatory disorders. Chronic use of NSAIDs is known to be associated with gastrointestinal and renal toxicity. Local generation of reactive oxygen species finally resulting in cellular apoptosis is one of the accepted mechanisms for NSAID-induced toxicity. Objective: The objective of the present study was to design and synthesize a series of 2-methane sulfonamido substituted arylthiazole derivatives by including structural features of combined antiulcer and anti-inflammatory activity utilizing as the structural core, thiazole nucleus with potential for antioxidant effect. Methods: Compounds were designed based on three dimensional and field similarity studies. The synthesized compounds were evaluated for their anti-inflammatory activity in carrageenan-induced rat paw edema model. Rofecoxib and indomethacin were taken as standard drugs for comparison. The in vitro antioxidant activity was assessed in potassium ferricyanide reducing power (PFRAP) assay employing ascorbic acid as the standard drug. Results: The compounds 6 and 7 showed good anti-inflammatory activity comparable to the standard group and were also non ulcerogenic at the test doses. Compounds 1-7 displayed varying degrees of reducing power in the PFRAP) assay and the methanesulphonamido derivatives 4-7 showed the highest antioxidant activity (EC50 values 3.7-5.1 μmol/ml vs ascorbic acid 7.4 μmol/ml). Theoretical ADME profiling of the compounds based on selected physicochemical properties showed excellent compliance with Lipinski’s rule. Conclusion: A series of compounds have been designed and synthesized having dual antioxidant and anti-inflammatory activity with activities comparable to standard drugs.
Keywords: Carrageenan-induced paw edema